Benefit Sharing Mechanisms: Agreements for watershed wellbeing - Consorcio para el Desarrollo Sostenible de la Ecorregion Andina (CONDESAN, 2011)
The correct handling of environmental services allows good environmental management which results in human wellbeing. Human beings that enjoy a state of wellbeing, have a greater capacity to realize good environmental management, ensuring therefore the provision of these services through a virtuous circle between human beings and the ecosystems they inhabit. However, there exist various difficulties in achieving good environmental management. In the case of water, those who benefit from its use oft en live in a different area from those who take care of the ecosystems where it is generated.